Libyan Economy and World Trade Organization - محمد عيسى (Dirasat in Economics and Business, 2008)
Our research involves an analysis of international commercial relations. It asses the impact of the Liberalization of the market in developing countries where The efficacy of production and distribution networks still needs to be re-inforced. The field study focuses on the inequitable relationship between Libya and the industryialized world within the context of the WTO agreement. It discusses the consequences of the Liberalization of the Libyan market prison to the adjustment of the economic system on the grounds of prof itability and effectiveness. Finally, we propose a series of solutions that allow progressive liberalization of comm.ercial traffic and minimize the impact of globalization and its accompanying financial ,monetary and commercial polices .